2010
DOI: 10.3109/00365599.2010.521189
|View full text |Cite
|
Sign up to set email alerts
|

GAD1 is a biomarker for benign and malignant prostatic tissue

Abstract: GAD1 is expressed in benign and malignant prostatic tissue and may serve as a highly prostate-specific tissue biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Increased GAD65 expression is a poor prognostic factor for both 1-year survival rates and mean survival times after surgery in patients with cholecystic cancer (10). Similar findings have also been reported in colon (11), breast (12), and prostate cancers (13). To the best of our knowledge, there are no reports of GAD 65 expression in SCLC, and the further accumulation of such cases is needed.…”
Section: Discussionsupporting
confidence: 64%
“…Increased GAD65 expression is a poor prognostic factor for both 1-year survival rates and mean survival times after surgery in patients with cholecystic cancer (10). Similar findings have also been reported in colon (11), breast (12), and prostate cancers (13). To the best of our knowledge, there are no reports of GAD 65 expression in SCLC, and the further accumulation of such cases is needed.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, high CMIP levels were associated with worse prognosis (recurrence-free and overall survival) in gastric and breast cancers [43,45] and were related with herceptin resistance in HER2-positive gastric cancer cells [46]. Similarly, the enzyme encoded by GAD1 gene, which catalyzes the conversion of L-glutamic acid to γ-aminobutyric acid, has been found overexpressed in several types of tumors, including lung adenocarcinoma [47], nasopharyngeal carcinoma [48], oral squamous cell carcinoma [49], prostate cancer [50], and brain metastasis [51], being also found upregulated in colon and HCC cells in vitro [52]. In parallel, high GAD1 levels were also shown to correlate with the pathological stage of patients with lung adenocarcinoma, positively correlating with metastasis and with worse recurrence-free survival [47].…”
Section: Discussionmentioning
confidence: 99%
“…Jaraj et al investigated the expression of GAD67 (GAD1) in the prostate and found that GAD67 expression was significantly higher in malignant and benign prostatic tissue than in non-prostatic control tissues. It was suggested that GAD67 may serve as a highly prostate-specific tissue biomarker (22). However, whether GAD 65 (GAD2) plays a similar role in malignancies of the gallbladder remains unknown.…”
Section: Discussionmentioning
confidence: 99%